2015
DOI: 10.1155/2015/534879
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Simulation-Based Communication Workshop on Resident Preparedness for End-of-Life Communication in the Intensive Care Unit

Abstract: Introduction. Although residents frequently lead end-of-life (EOL) discussions in the intensive care unit (ICU), training in EOL care during residency has been required only recently, and few educational interventions target EOL communication in the ICU. This study evaluated a simulation-based intervention designed to improve resident EOL communication skills with families in the ICU. Methods. Thirty-four second-year internal medicine residents at a large urban teaching hospital participated in small group ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 27 publications
0
38
0
1
Order By: Relevance
“…But it will be important to overcome the many barriers to the underutilization of these services [25, 26], including low levels of knowledge of hospice and palliative care services among patients, religious beliefs, fatalism (a concept that everything is pre-decided), physician discomfort with discussing palliative care referral [27], lack of education about palliative care in nephrology fellowships, and financial disincentives [20, 28, 29]. Basic palliative care skills can be acquired by attending continued medical education accredited workshops [30]. However, to observe a substantial change in clinical practice style, a more rigorous primary palliative care curriculum across all the nephrology fellowship programs is necessary [29].…”
Section: Discussionmentioning
confidence: 99%
“…But it will be important to overcome the many barriers to the underutilization of these services [25, 26], including low levels of knowledge of hospice and palliative care services among patients, religious beliefs, fatalism (a concept that everything is pre-decided), physician discomfort with discussing palliative care referral [27], lack of education about palliative care in nephrology fellowships, and financial disincentives [20, 28, 29]. Basic palliative care skills can be acquired by attending continued medical education accredited workshops [30]. However, to observe a substantial change in clinical practice style, a more rigorous primary palliative care curriculum across all the nephrology fellowship programs is necessary [29].…”
Section: Discussionmentioning
confidence: 99%
“…Given this discrepancy in advance care planning documentation among racial/ethnic minority patients with HM, it is important that providers are educated about the need for culturally sensitive communication that will engage their patients from different backgrounds. 30 In addition, it is important to acknowledge that standard definitions of high intensity care at the end of life may not have the same meaning for patients with HM, given that chemotherapy regimens for these diseases tend to require more inpatient admissions and also because the persistent prospect of cure remains, even in advanced disease. More observational studies of patient-reported outcomes of patients with HM at the end of life are needed to gain a better understanding of the unique needs of this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…After participating in the course, residents were more comfortable discussing end-of-life care, leading family meetings, and displaying empathy. 67 Another observational interventional study evaluated family member perceptions of residents communication ability after undergoing specialized training sessions. Residents who participated in at least two communication training sessions were perceived by family members to have addressed their informational and emotional needs.…”
Section: Training In Family Centered Carementioning
confidence: 99%